Fuzzy Multi-Criteria Decision Making in Human Resource Selection Procedure: A Case Study of Indian IT Industry - Mittal , K. C.; Goel , Ashok Kumar; Mohtndru , Pankaj (Gyan Management Journal, 2009)
This paper aims to discuss the considerable theoretical and practical issues in employee selection and recruitment processes of leading Indian Information Technology (IT) companies like TCS and H CL. Further, the author aims to have a profound understanding as to how these selection strategies in the recruitment and selection procwes based upon multiple criteria. e11able to be simulated. An effort is made through this paper to evolve an optimal and accurate judgement according to the human thinking model and also Lo mitigate the commonly occurred biases in human recruitment and selection procedures. The main purposes of the work are to discuss the appointment of best possible candidate through fua:y logic based upon few major criteria's, to construct a model for evaluatiori of best talent, and accordingly to develop a Decision support system (DSS) in human re.source selection.
Keywords: Decision support system; selection strategies; selection pr'ocesses